Systematic Review and Meta-Analysis of the Efficacy and Safety of Combined Epinephrine and Corticosteroid Therapy for Acute Bronchiolitis in Infants - Kok P. Kua; Kok P. Kua; Shaun W. H. Lee (Frontiers Media S.A., 2017)
Objective: To evaluate the effectiveness of combined epinephrine and corticosteroid therapy for acute bronchiolitis in infants.Methods: Four electronic databases (MEDLINE, EMBASE, CINAHL, and CENTRAL) were searched from their inception to February 28, 2017 for studies involving infants aged less than 24 months with bronchiolitis which assessed the use of epinephrine and corticosteroid combination therapy. The methodological quality of the included studies was assessed using the Cochrane Collaboration's Risk of Bias Tool. A random-effects meta-analysis was used to pool the effect estimates. The primary outcomes were hospital admission rate and length of hospital stay.Results: Of 1,489 citations identified, 5 randomized controlled trials involving 1,157 patients were included. All studies were of high quality and low risk of bias. Results of the meta-analysis showed no significant differences in the primary outcomes. Hospitalization rate was reduced by combinatorial therapy of epinephrine and corticosteroid in only one out of five studies, whereas pooled data indicated no benefit over epinephrine plus placebo. Clinical severity scores were significantly improved in all five RCTs when assessed individually, but no benefit was observed compared to epinephrine monotherapy when the data were pooled together. Pooled data showed that combination therapy was more effective at improving oxygen saturation level (mean difference: −0.70; 95% confidence interval: −1.17 to −0.22, p = 0.004). There was no difference in the risk of serious adverse events in infants treated with the combined epinephrine and corticosteroid therapy.Conclusions: Combination treatment of epinephrine and dexamethasone was ineffective in reducing hospital admission and length of stay among infants with bronchiolitis.